Procedures for recovering cassava clones distributed in vitro - Roca, W.; Rodríguez, J.A.; Mafla, G.; Roa E, Julio César (International Center for Tropical Agriculture, 1984)
Guidelines are provided to acquaint the personnel of national programs and other collaborators with the procedures to recover, propagate, and transplant culture materials after their arrival. These include: (1) recovery of the cultures by direct potting of cassava plants after short trips; 1 wk. of 2000 lux illumination, 14-h photoperiod, and 26-28 degrees Celsius temp., after 1-2 wk.- trips; and aseptical excision of available green axillary or terminal bud growth, before proceeding to micropropagation, after trips lasting more than 3 wk.; (2) micropropagation for which procedures, equipment, and illustrations are given, and suppliers are listed; (3) potting, listing the procedures and needed items and including illustrative pictures; (4) explanation of field transplantation procedures and conditions needed for successful results. Brief background information on in vitro methods for the international exchange of cassava clones is presented, as well as complementary references. (CIAT)